Förderung von digitalisierungsbezogenen Kompetenzen von angehenden Physiklehrkräften mit dem SQD-Modell im Projekt DiKoLeP - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Lehr-Lern-Labore und Digitalisierung)

Von der "Shallowing Hypothese" zur "Illusion of Understanding" -wie wirken Erklärvideos und Lehrbuchtexte auf Wissen und Verstehensillusion? - Kulgemeyer, Christoph; Sterzing, Fabian; Hörnlein, Madeleine

"Aus Erklärvideos lernt man nur oberflächlich" - oder erwirbt man auch Konzeptwissen? - Hörnlein, Madeleine; Kulgemeyer, Christoph

Forschungsdatenmanagement erleichtern durch relationale Datenbanken: Ein Datenmodell für naturwissenschaftsdidaktische Forschung - Buschütter, David; Zeller, Jannis; Oltmanns, Stefan; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Vogelsang, Christoph (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Entwicklung von Schülervorstellungen zu NOS & NOSI im Physikunterricht - Zwick, Linda; Webersen, Yvonne; Wodzinski, Rita (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Entwicklung und Evaluation einer NdN-Unterrichtsreihe zur Unterstützung von Lernpfaden - Webersen, Yvonne (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

How authenticity impacts validity: Developing a model of teacher education assessment and exploring the effects of the digitisation of assessment methods Über Validität und Authentizität: Effekte des Transfers von Testinstrumenten in ein digitales Format auf die erhobenen Aspekte der professionellen Handlungskompetenz - Kulgemeyer, Christoph; Riese, Josef; Vogelsang, Christoph; Buschhüter, David; Borowski, Andreas; Weißbach, Anna; Jordans, Melanie; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Abstract Based on a literature review of studies on teachers’ professional competence and related assessment tools, this paper introduces a model of teacher education assessment. It is influenced by Miller’s (1990) framework of assessment in medical education and includes, among other aspects, performance assessments. This model is used to understand the potential effects of transferring assessment tools into a digital format with assessment feedback. Five examples for such a transfer will be discussed: three methods for various aspects of communication, a test for pedagogical content knowledge, and a test for content knowledge. All five are established instruments well-described in terms of validity. All five have recently been transferred into a digital format. The analysis of this transfer also reveals a potentially harmful effect of digital assessment. The closer an assessment instrument is to assessing action-related parts of professional competence, the more authenticity is required; however, digitisation tends to decrease this authenticity. This suggests that an increasing number of digital assessment tools in teacher education might result in an even more dominant focus on knowledge tests, ignoring other parts of professional competence. This article highlights the role of authenticity in validity and discusses the most suitable assessment format to address various parts of professional competence. It ends by highlighting the lessons learned from the transfer of assessment instruments into a digital format that other academic disciplines might find interesting.
Keywords: Education

Erwerb und Messung fachdidaktischen Wissens zum Einsatz digitaler Medien - Große-Heilmann, Rike Isabel; Burde, Jan-Philipp; Riese, Josef; Schubatzky, Thomas; Weiler, David (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Unterrichtsplanung mit sinnvoller Einbettung digitaler Medien im PU - Jordans, Melanie; Riese, Josef (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Datenbasierte Fähigkeitsprofile im Physikdidaktischen Wissen - Zeller, Jannis; Riese, Josef (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)